STUDI TENTANG ’ELIT INDONESIA’: PROBLEMATIKA & PENDEKATAN - Thung, Ju Lan (Jurnal Masyarakat dan Budaya, 2015)
Even though the term ’elite’ is often used by the Indonesian researchers, but it is rather difficult to find a particular study that focuses on the Indonesian elite(s). We could find some historical writings concerning Indonesian elite of the 20th century, but not contemporary studies on the Indonesian elite(s), particularly those using anthropological approaches. This paper discusses the methodological problems which are faced by the Indonesian researchers to conduct an anthropological study of elite.